Global and regional estimation and evaluation of suitable roof area for solar and green roof applications - Diana Ürge-Vorsatz; Souran Chatterjee; Luisa F. Cabeza; Gergely Molnár (Developments in the Built Environment)
Buildings contribute to 40% of energy consumption and 30% of CO2 emissions in 2019 globally, therefore it is necessary to exploit different solutions to decrease the corresponding energy demand, including green and cool roofs as well as on-site energy generation. To evaluate the potential of such technologies, one major input data for models and calculations is the available roof area, yet the literature shows a huge knowledge gap in this regard. Therefore, this paper contributes to filling this gap by estimating the roof availability over the period 2022–2060, using the detailed regional projections of the BISE (Building Integrated Solar Energy) model. Our results show that the roof area is likely to increase globally and in most of the analysed regions over the forthcoming decades, driven primarily by newly built tertiary buildings. In European context, the future increase of commercial/public rooftops is projected to be more pronounced for the western countries, although the overall growth is predicted to be slightly offset by shrinking residential rooftops both in the western and eastern regions. This study also demonstrates that despite the shading-related uncertainties of the estimation, the dimension of the available rooftop area could ensure significant potential for energy production and thermal regulation.